Методы оценки надежности телекоммуникационных систем - Килячков, К. П. (ХНУРЭ, 2011)
The work discussed the relevance of the use of accessible assessments in telecommunica tions networks. To receive them calculated the most well-known estimates, and given the com parative data.
Keywords: телекоммуникационные услуги; эффективность телекоммуникационных систем